ACADEMIC CULTURE BARRIERS FACED BY ENGLISH DEPARTMENT STUDENTS JOINING INTERNATIONAL INTERNSHIP PROGRAM - Ramadhani, Wulan; Poedjiastutie, Dwi (University of Muhammadiyah Malang, 2020)
Academic culture barrier is one of the barriers that students faced when they were going abroad whether for studying or doing their internship. There are lots of students’ encounters a problem when they were doing their internship. This research was conducted to examine the academic culture barriers faced by ELED students joining the international internship program to Thailand. In conducting the research, the researcher utilized the descriptive qualitative design to obtaining formation related to the problem in academic life. The participants of this study were eight students of ELED UMM who join the international internship program in Thailand 2018. The researcher used semi-structured interviews and open-ended questionnaire in order not to limit participants in telling their experience. The results of this study are divided into 3 categories which are academic problems, solutions, and academic differences. The academic problems that the participants faced involve language, English knowledge, the use of Thai letters, curriculum, and students’ participation. The solution that they gave were using gesture in dealing with the language problem, using role-play in dealing with lack of knowledge in English, teach the students alphabet in dealing with the using of Thai letters, designing their own material in dealing with no exact curriculum, and try to interact to the students outside the class in dealing with passive students participation. Furthermore, the academic differences are the relationship between student and teacher, and school culture.